2020
DOI: 10.1021/acsomega.0c03069
|View full text |Cite
|
Sign up to set email alerts
|

Coal Classification Method Based on Improved Local Receptive Field-Based Extreme Learning Machine Algorithm and Visible–Infrared Spectroscopy

Abstract: In the process of using coal, if the type of coal cannot be accurately determined, it will have a significant impact on production efficiency, environmental pollution, and economic loss. At present, the traditional classification method of coal mainly relies on technician’s experience. This requires a lot of manpower and time, and it is difficult to automate. This paper mainly studies the application of visible-infrared spectroscopy and machine learning methods in coal mine identification and analysis to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Deep architectures can reduce the variance introduced by solid samples, which have variable path lengths due to scattering. Deep architectures are used in NIR to determine the quality of medicines [125][126][127]157], meats, vegetables and fruits [128][129][130][131][132], the contents of soil and minerals [13,[133][134][135]158], cracks in water pipes [136], the manufacturing date of paper [159], and water pollution [137], as well as in the cursory evaluation of malady [160]. Experiments conducted on four distinct datasets containing solid samples demonstrated that the number of training samples influences the generalization ability of deep learning algorithms [140,141].…”
Section: Discussionmentioning
confidence: 99%
“…Deep architectures can reduce the variance introduced by solid samples, which have variable path lengths due to scattering. Deep architectures are used in NIR to determine the quality of medicines [125][126][127]157], meats, vegetables and fruits [128][129][130][131][132], the contents of soil and minerals [13,[133][134][135]158], cracks in water pipes [136], the manufacturing date of paper [159], and water pollution [137], as well as in the cursory evaluation of malady [160]. Experiments conducted on four distinct datasets containing solid samples demonstrated that the number of training samples influences the generalization ability of deep learning algorithms [140,141].…”
Section: Discussionmentioning
confidence: 99%
“…This method has the advantages of fast learning speed and good generalization performance. [18][19][20] Taking the Raman spectra of the samples of various brands collected with the integration time of 80 s as an example, the original data were first introduced into an extreme learning machine algorithm, with 72% of the samples as test sets (54 samples) and 28% as training sets (21 samples). The sample selection was random and ran 200 times.…”
Section: Pretreatment Analysis Of Raman Spectra Of Cheese Productsmentioning
confidence: 99%
“…Literature [18] holds that internal control should be taken as the starting point to improve the management level of SR projects and the use efficiency of funds. Literature [19] holds that strengthening the performance evaluation of SR funds should start from two aspects: the use benefit evaluation of SR funds and the benefit of SR work. Paying attention not only audits compliance, legality, rationality, and authenticity of the income and expenditure of SR projects but also comprehensively evaluates their economic benefits, technical benefits, and social benefits.…”
Section: Related Workmentioning
confidence: 99%